The deserving and the undeserving: "heuristics" or "automatism"? - Peter Grand; Guido Tiemann (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2020)
Recent contributions have cogently addressed the effect of public opinion on the construction and reform of social security systems. This contribution focuses on public sentiments concerning the conditionality of unemployment benefits. We exploit a vignette experiment that was embedded with Round 8 of the European Social Survey. Across the set of twenty-three different countries/survey segments, respondents were randomly assigned different vignettes that characterize the age and family status of benefit claimants who turn down job offers due to lower payment or qualification levels or are unwilling to carry out unpaid community work in return for social transfers. Survey respondents are then inquired whether they support which level of sanctions or cuts to these benefit claimants. Our empirical findings demonstrate that deservingness cues provide strong and robust causal effects. The observational controls, which pick up material self-interest and ideological standings, are also closely linked with the outcome variable. Eventually, these effects are conditioned by the respective national contexts.
Keywords: 330